Prediction of storm impacts on beach and dune systems - Ciavola, Paolo (2018)
This chapter provides an overview of the current knowledge of storm impacts on low-lying coastlines, including beaches and dunes. It first outlines the complexity of identifying a storm event in an objective manner. The impact of storms on dune ridges is then discussed, making a comparison between research recently carried out in both the USA and Europe. The main impacts of storm events are also reviewed, taking into account the development of overwash processes and breaching of the dune system as well as flooding of the hinterland. The chapter also provides a detailed overview of qualitative and quantitative models of dune erosion by considering the most advanced numerical techniques. It finally discusses the methods for hazard and risk evaluation, taking into account the emerging role that early warning systems are playing in this field.